The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1017/edp.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of School Belonging for Young Children With Refugee Backgrounds

Abstract: Previous research with adolescents with refugee backgrounds living in countries of resettlement has found that school belonging impacts upon a range of wellbeing and developmental outcomes, including mental health, peer relationships, self esteem and self efficacy, and academic achievement.However, very little research has explored school belonging in younger children with refugee backgrounds (that is, less than 13 years of age). In this paper, we report on a participatory research project concerning the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 31 publications
0
37
0
1
Order By: Relevance
“…The emphasis on cultural assimilation in Quebec’s classes d’accueil appears particularly strong in comparison to similar programs in other white-settler nations. For instance, studies on intensive English language schools or centres in Australia reveal the tendency of such programs to adopt a more holistic and sociocultural approach to education and learning [9,13,14,17]. In such environments, young people’s knowledge and values are recognised and celebrated.…”
Section: Navigating Resettlement: Experiences In “Formal” Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis on cultural assimilation in Quebec’s classes d’accueil appears particularly strong in comparison to similar programs in other white-settler nations. For instance, studies on intensive English language schools or centres in Australia reveal the tendency of such programs to adopt a more holistic and sociocultural approach to education and learning [9,13,14,17]. In such environments, young people’s knowledge and values are recognised and celebrated.…”
Section: Navigating Resettlement: Experiences In “Formal” Spacesmentioning
confidence: 99%
“…For those who make their way to Canada, war-related mental health distress may occur alongside poverty, discrimination, isolation, language barriers and difficulties in school [6,7]. Studies on young people with refugee backgrounds in Australia point to similar resettlement realities [8,9,10,11,12,13,14,15,16,17]. With growing numbers of asylum claimants and their families receiving permanent residency—and becoming interwoven in the Canadian social fabric—it is critical that psychosocial programs and interventions address their needs, as individuals, families and communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, however, it is important for health education approaches to remain cognisant of the limits to too simple a focus on developing children's capacities and strengths and to recognise and respond to the disabling effects of social context on migrant children's opportunities for health. Forms of health education that acknowledge, and successfully address, the socially located barriers to children's health-enhancing practices (including experiences of stigma, discrimination and social exclusion) may prove helpful in enhancing social integration and wellbeing of young migrants (Brun, 2001;Due et al, 2016;Fernandes et al, 2014;Posselt et al, 2015;Sampson and Gifford, 2010). Research from Europe highlights the crucial role health care professionals and providers play in shaping attitudes towards migrants and their engagement with health care services (Dias et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Given the variation in prevalence rates noted above, it is important to note that a number of risk and protective factors have been found to influence whether or not, and to what extent, children with refugee or asylum seeker backgrounds experience psychological distress or positive wellbeing outcomes following resettlement within countries such as Australia (Correa-Velez, Gifford, & McMichael, 2015;Fazel et al, 2012;McFarlane, Kaplan, & Lawrence, 2011). Indeed, research has indicated that post-settlement factors have a critical impact on child wellbeing, including through areas, such as education, social inclusion, and interaction with health services (Correa-Velez et al, 2015;Due, Riggs, & Augoustinos, 2016). In congruence with the ecological model of health (Miller & Rasmussen, 2016), which places emphasis on a child's wellbeing occurring within "the context of their interactions with different layers of the environment" (Correa-Velez, Gifford, & Barnett, 2010, p. 1401, previous research has identified relevant influences occurring at individual, family, community and societal levels (Fazel et al, 2012).…”
Section: Background and Previous Literaturementioning
confidence: 99%